Differential Tissue-Specific Jasmonic Acid, Salicylic Acid, and Abscisic Acid Dynamics in Sweet Cherry Development and Their Implications in Fruit-Microbe Interactions - Fresno, David H.; Munné-Bosch, Sergi (Frontiers in Plant Science, 2021)
Sweet cherry is an important non-climacteric fruit with a high commercial interest, but exploitation of sweet cherry trees (Prunus avium L.) in orchards is usually subject to important economic losses due to fruit decay by pathogenic fungi and other microorganisms. Sweet cherries development and ripening are characterized by profound physiological changes in the fruit, among which the phytohormone abscisic acid plays a pivotal role. In addition, sweet cherries are usually affected by fruit decay pathogens, and the role of other stress-related hormones such as jasmonic and salicylic acid may also be of paramount importance, not only from a developmental point of view, but also from a fruit-microbe interaction perspective. Here, a tissue-specific hormone quantification by LC-MS/MS, including the contents of jasmonic acid, salicylic acid and abscisic acid, in the fruit exocarp and mesocarp of sweet cherries during fruit development from trees growing in a commercial orchard was carried out. Additionally, this study was complemented with the characterization of the culturable epiphytic and endophytic microbial communities of sweet cherries at various stages of fruit development and during cracking lesion formation. Our results revealed a completely differential behavior of phytohormones between both tissues (the exocarp and mesocarp), with a more dynamic exocarp in front of a more stable mesocarp, and with marked variations during fruit development. Microbial epiphytic community was mainly composed by yeasts, although rot-causing fungi like Alternaria spp. were always also present throughout fruit development. Endophytic colonization was poor, but it increased throughout fruit development. Furthermore, when the exocarp was naturally disrupted in sweet cherries suffering from cracking, the colonization by Alternaria spp. markedly increased. Altogether, results suggest that the fruit exocarp and mesocarp are very dynamic tissues in which endogenous phytohormones not only modulate fruit development and ripening but also fruit-microbe interactions.